The Effects of the Tri Hita Karana Culture, Computer Anxiety, Computer Attitude, and Computer Self Efficacy on the Interest of Accounting Students of Private Universities in Denpasar City to Use Accounting Software - Ernawatiningsih, Ni Putu Lisa; Apriada, Kadek (AIBPM Publisher, 2020)
This study aims to analyze the effect of the Tri Hita Karana (THK) culture, computer anxiety, computer attitude, and computer self-efficacy on the interest of accounting students of private universities in Denpasar City to use accounting software. Sample of this research is 95 accounting students was taken using random sampling techniques. Data were analysed using multiple linear regression analysis and the result of this study finds that Tri Hita Karana and computer attitude has positively affected the interest of accounting students to use accounting software, but computer anxiety and compter self-efficacy does not affect the interest of accounting students to use accounting software. The implications of this research for private universities in Denpasar City are expected to be able to improve the quality of the learning process and provide insight for students regarding the use of accounting software so as to produce graduates who can compete in the workforce later.